Pengaruh Likuiditas dan Ukuran Perusahaan terhadap Profitabilitas pada Perusahaan Subsektor Perbankan yang Terdaftar di BEI Tahun 2020-2023 - Putra, Kgs. Rafly Assidhes; Msy Mikial; Armereo, Crystha (CV. Doki Course and Training, 2025)
Abstract : This study aims to determine the effect of liquidity and company size on profitability in banking sub-sector companies listed on the Indonesia Stock Exchange in 2020-2023, both simultaneously and partially. The population in this study amounted to 47 banking companies listed on the Indonesia Stock Exchange in the banking sub-sector. The research sample amounted to 16 companies taken using purposive sampling techniques. The type of data used is secondary data from financial reports published by each company and uses multiple linear regression analysis techniques. The results of this study indicate that liquidity and company size affect profitability with a calculated F value of 3.155 greater than the F table of 3.150 and a significance value of 0.050